'Let's Talk About Children': Investigating the Use of a Family‐focused Intervention in the Gambling Support Services Sector. Issue 3 (22nd October 2017) - von Doussa, Henry; Sundbery, Jacqui; Cuff, Rose; Jones, Sarah; Goodyear, Melinda
Abstract : The family‐focused mental health intervention, 'Let's Talk About Children, ' has positively influenced the lives of families affected by parental mental illness. This paper outlines the use of this brief, strengths‐based intervention for parents with gambling and other co‐occurring issues from the gamblers' support services sector. Over a six‐month period, a training manual and accompanying resources were adapted for the gamblers' support services sector and a targeted training session developed. Nine problem gambling counsellors from three Victorian gambling support services trialled the Let's Talk About Children intervention over a four‐month period. Qualitative data were gathered through focus groups, interviews, and practice enquiry groups to determine the impact of the Let's Talk About Children model for gambling support services. The results are presented as 'practice wisdoms and recommendations' reporting on the impact of the trial and to provide some guidance to support others in the implementation of a specific family‐focused intervention. This paper reports on the first exploratory trial of Let's Talk About Children for the gambler's support services sector in Australia.